2018
DOI: 10.1140/epja/i2018-12447-0
|View full text |Cite
|
Sign up to set email alerts
|

The nucleon as a test case to calculate vector-isovector form factors at low energies

Abstract: Abstract. Extending a recent suggestion for hyperon form factors to the nucleon case, dispersion theory is used to relate the low-energy vector-isovector form factors of the nucleon to the pion vector form factor. The additionally required input, i.e. the pion-nucleon scattering amplitudes are determined from relativistic next-to-leading-order (NLO) baryon chiral perturbation theory including the nucleons and optionally the Delta baryons. Two methods to include pion rescattering are compared: a) solving the Mu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 62 publications
2
15
0
Order By: Relevance
“…The extracted proton charge radius is consistent with our result, but as noted in Ref. [59], this approach is subject to uncertainties in the ρ-region, different from the exact representation used in the papers discussed above.…”
Section: Short History Of Dispersive Analyses Of the Nucleon Form Factorssupporting
confidence: 91%
“…The extracted proton charge radius is consistent with our result, but as noted in Ref. [59], this approach is subject to uncertainties in the ρ-region, different from the exact representation used in the papers discussed above.…”
Section: Short History Of Dispersive Analyses Of the Nucleon Form Factorssupporting
confidence: 91%
“…The isoscalar and isovector form factors of the nucleon have all non-vanishing "charges". One can define an isoscalar and an isovector radius based on (42), see, e.g., [3,19]. Those two radii are positive and in the order of 1 fm, in full agreement with (43).…”
Section: Qed Type Case and Form Factor Parametrizationsupporting
confidence: 60%
“…From a technical point of view, these relations are easy to deduce from the definitions of the helicity amplitudes (3). Later, the constraint (4) will be very important for our model independent low-energy parametrization of the transitions.…”
Section: Transitionmentioning
confidence: 99%
“…The B (E2) data of Pd [102][103][104][105][106][107][108][109][110][111][112] and Ru 96-102 nuclei were examined [12][13][14]. Several vibrational-gamma soft properties IBM calculations have been reported that dealt with the IBM and IVBM models [15][16][17][18][19]. The aim of the present work is to interpret the collective behavior of yrast state of 124 Te nucleus by D-G, IBM-1, BM, and IVBM models.…”
Section: Introductionmentioning
confidence: 99%